Modulation of Kv3.1/Kv3.2 promotes gamma oscillations by rescuing Aβ‐induced desynchronization of fast‐spiking interneuron firing in an AD mouse model in vitro. (7th July 2020) - Andrade‐Talavera, Yuniesky; Arroyo‐García, Luis Enrique; Chen, Gefei; Johansson, Jan; Fisahn, André
Abstract : Key points: Gamma oscillations (30–80 Hz) are important for cognitive functions and depend on the synchronized activity of fast‐spiking interneurons (FSN), which is crucial for network stability. Gamma oscillations are degraded in Alzheimer's disease (AD) patients exhibiting cognitive impairment, with the degree of cognitive decline correlating with the severity of gamma disruption in response to neurotoxic amyloid‐beta peptide (Aβ). Small molecule compounds EX15 and RE01 modulate Kv3.1/Kv3.2 potassium channels on FSN, resulting in faster activation kinetics and increased firing frequency, suggesting direct consequences for cognition‐relevant gamma oscillations, particularly in a situation where network activity is pathologically compromised in the presence of neurotoxic Aβ. Using electrophysiological techniques in an in vitro AD model, we found a significant effect of EX15 and RE01 with respect to counteracting toxic Aβ effects on neuronal dynamics, advocating for targeting FSN activity to rescue cognitive performance from impairment caused by neurodegenerative triggers. Abstract: Rhythmic electrical activity in neuronal networks such as gamma oscillations (30–80 Hz) underlies cognitive functions such as sensory perception, attention and memory. Gamma oscillations are disrupted in Alzheimer's disease (AD) patients and animal AD models, with the severity of cognitive decline correlating with the degree of rhythm disruption. Misfolded amyloid‐β peptide (Aβ) is assumed to be a key trigger of AD pathology and has been show to de‐synchronize action potential firing in fast‐spiking interneurons (FSN), which is crucial for entraining neuronal network activity into the gamma rhythm. The synchronizing activity of FSN therefore has become one of the most suitable targets to counteract disease‐driven degradation of gamma oscillations and consequent cognitive decline. EX15 and RE01 are small‐molecule compounds that modulate Kv3.1/Kv3.2 potassium channels, resulting in faster activation kinetics and increased FSN firing frequency. In the present study, we investigated the potential pro‐cognitive effects of EX15 and RE01 by testing their ability to modulate FSN activity during ongoing gamma oscillations in normal and Aβ‐disrupted network states in mouse hippocampus in vitro . In the compromised, but not the uncompromised, network state with gamma oscillations partially disrupted by Aβ, both compounds improve gamma oscillation regularity by promoting re‐synchronization of FSN action potential firing. Our data suggest a therapeutic potential for compounds such as EX15 and RE01, which can rescue normal action potential firing parameters in FSN, in the search for disease‐modifying drug candidates counteracting the progressive dysfunction of neuronal network dynamics that underlies the cognitive impairment typical of AD and other cognitive brain disorders. Key points: Gamma oscillations (30–80 Hz) are important for cognitive functions and depend on the synchronized activity of fast‐spiking interneurons (FSN), which is crucial for network stability. Gamma oscillations are degraded in Alzheimer's disease (AD) patients exhibiting cognitive impairment, with the degree of cognitive decline correlating with the severity of gamma disruption in response to neurotoxic amyloid‐beta peptide (Aβ). Small molecule compounds EX15 and RE01 modulate Kv3.1/Kv3.2 potassium channels on FSN, resulting in faster activation kinetics and increased firing frequency, suggesting direct consequences for cognition‐relevant gamma oscillations, particularly in a situation where network activity is pathologically compromised in the presence of neurotoxic Aβ. Using electrophysiological techniques in an in vitro AD model, we found a significant effect of EX15 and RE01 with respect to counteracting toxic Aβ effects on neuronal dynamics, advocating for targeting FSN activity to rescue cognitive performance from impairment caused by neurodegenerative triggers.